Geodiversity assessment as a first step in designating areas of geotourism potential. Case study: south-east Pałuki (Middle Poland) - Górska-Zabielska , Maria; Błaszczyk, Natalia; Nowak, Izabela (Acta Geographica Lodziensia, 2024)
The rich and varied geological heritage of south-eastern Pałuki is not widely known, and therefore the regional authorities do not link it to improving the quality of life of inhabitants; hence, they do not manage geotourism resources. Pałuki is characterised by a unique geodiversity, which has a great potential for diversifying the (geo)tourist offer. It can be used for pro-environmental geo-education and promotion of the region. Interesting and uniquely developed geotourism resources available locally are an effective driving force for sustainable development of local self-governing units, not only in peripheral tourist areas. The objective of this study is to examine the potential for the development of geotourism in the context of the existing but hitherto under-appreciated geodiversity in the north-east of Wielkopolska. The study is also intended to facilitate the transfer of knowledge about the distinctive geodiversity of the research area, with the aim of raising the ecological awareness of those who have received pro-environmental geodiversity education. The mission of the article is also to promote the region. The paper presents a valorisation analysis of twelve geotourism sites qualified for detailed field and chamber studies. A qualitative analysis was carried out, taking into account geomorphological, additive and utilitarian categories, and unique analytical criteria were applied due to the specificity of the study area. The results of the analytical part made it possible to identify the most valuable and geotouristically attractive geostations. They form two original geotourist trails under the common name “Georóżnorodne Pałuki” (“Geodiverse Pałuki”).